2014
DOI: 10.1186/1756-0500-7-888
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of anemia among pregnant women of Mekelle town: a cross sectional study

Abstract: BackgroundNutritional anemia is the most common type of anemia worldwide and mainly includes iron, folic acid, vitamin B12 and vitamin C deficiencies. Anemia is a global public health problem affecting people in all age groups but the burden of the problem is higher in pregnant women. The study aimed to assess prevalence of anemia and associated factors among pregnant women attending antenatal care in governmental health institutions in mekele town.MethodsInstitution based cross-sectional study was employed. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
108
5
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(150 citation statements)
references
References 13 publications
29
108
5
8
Order By: Relevance
“…These findings are supported by previous analyses in Ethiopia [6,7,10,15]. Pregnancy increases the requirements for iron in the body and often multiple pregnancies deplete the iron stores in the women's body, especially if they are closely spaced.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings are supported by previous analyses in Ethiopia [6,7,10,15]. Pregnancy increases the requirements for iron in the body and often multiple pregnancies deplete the iron stores in the women's body, especially if they are closely spaced.…”
Section: Discussionsupporting
confidence: 86%
“…schistosomiasis, hookworm infection), prior use of contraceptives, use of iron supplementation, birth spacing/intervals, parity and gravidity, educational attainment, age, body weight, trimester of pregnancy and wealth status. [6][7][8][9][10][11][12][13][14][15][16][17][18]. The relationship between anemia and dietary practices in Ethiopia has shown mixed results [12,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The finding of this study is consistent with study conducted in Ethiopia showed that 21.3% of pregnant women were anemic. 12,13,14,15,16 The finding of this study is inconsistent with other study which is done in Western Nepal, Morang District and Eastern Nepal were 41.0 percent, 47.24% and 46.6% respectively prevalence of anemia among pregnant women. 17,18 Finding is also inconsistent with the national data showed that the prevalence of anemia among pregnant were 46 %.…”
Section: Discussioncontrasting
confidence: 85%
“…Based on the guidelines of micronutrient deficiency prevention and control, all ANC attending mothers are counseled for the benefit of adequate nutrition. In addition, they are also screened for presence of absence of some diseases including anemia [36]. In the current study, mothers who didn't fully attend the four WHO recommended visits were twice more likely to be anemic than mothers who fully attended all the recommended ANC visits, AOR=2.37 (95% C.I.…”
Section: Discussionmentioning
confidence: 62%